Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/dss.0000000000001203
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Hydroxylapatite Dermal Filler for Treatment of Dorsal Hand Volume Loss: Results From a 12-Month, Multicenter, Randomized, Blinded Trial

Abstract: Treatment with CaHA results in significant improvement in the appearance of the dorsal hand and is well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 13 publications
1
35
0
5
Order By: Relevance
“…10,12 This scale has been used successfully in other studies of hand-volumizing treatment with dermal fillers and has demonstrated consistent intrarater and interrater agreement. 6,10,12,14 Improvements observed in the MHGS have previously corresponded to improvements in GAIS ratings and subject satisfaction. 6,14 These correlations were also corroborated in the current study and support the clinical relevance of the favorable aesthetic results with this hyaluronic acid product.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…10,12 This scale has been used successfully in other studies of hand-volumizing treatment with dermal fillers and has demonstrated consistent intrarater and interrater agreement. 6,10,12,14 Improvements observed in the MHGS have previously corresponded to improvements in GAIS ratings and subject satisfaction. 6,14 These correlations were also corroborated in the current study and support the clinical relevance of the favorable aesthetic results with this hyaluronic acid product.…”
Section: Discussionmentioning
confidence: 76%
“…Although various products have been used to restore dorsal hand volume loss such as poly- l -lactic acid and calcium hydroxylapatite, at the time of this research study, there was only one non–hyaluronic acid product approved by the U.S. Food and Drug Administration for this indication (i.e., calcium hydroxylapatite). 5,6 However, a small open-label study provided promising results with small-gel-particle hyaluronic acid for the correction of volume loss in the dorsal hand. 7 Fat injections have been used for replenishing the volume deficits.…”
mentioning
confidence: 99%
“…Clinical trials have demonstrated statistically significant improvement in dorsal hand volume after treatment with CaHA and even maintenance of these aesthetic results for up to 12 months after a single treatment. 13,14 Adverse events with this filler include temporary bruising and swelling, and rarely nodules that do not affect hand function. 14 Goldman et al 15 first reported the use of the efficacy and superiority of HA over collagen for dorsal hand augmentation.…”
Section: Dermal Fillersmentioning
confidence: 99%
“…13,14 Adverse events with this filler include temporary bruising and swelling, and rarely nodules that do not affect hand function. 14 Goldman et al 15 first reported the use of the efficacy and superiority of HA over collagen for dorsal hand augmentation. Recently, a small-particle hyaluronic acid (SPHA) injectable gel with lidocaine has been approved by the FDA for dorsal hand rejuvenation after demonstrating efficacy in further clinical trials.…”
Section: Dermal Fillersmentioning
confidence: 99%
“…In a recent multicenter, randomized, controlled, single-blinded study, treatment has been shown to have a duration of effect of at least 12 months following a single procedure and is very well tolerated, with adverse events restricted to mild-to-moderate injection-site reactions and without issues relating to hand function. 19 …”
Section: Introductionmentioning
confidence: 99%